El discurso, el poder y el arte de gobernar. Consideraciones teórico-prácticas para el análisis del discurso jurídico-político - Carvajal Pardo, Alejandro (2023)
Law is a political phenomenon, and politics operates within the institutional field created by law. This article explores the linguistic dimension that is common to both law and politics, since both are semantic and rhetorical constructs. The author examines theories proposed by two authors (Michel Foucault and Teun van Dijk), as well as those connections existing between them, referring constantly to the State as a problem in discourse, in order to set the foundations for a possible analysis of political and legal discourse.